Physical preparedness of young athletes in jiu-jitsu at the initial stage of sports specialization (dynamics and impact on athletic performance) - T.M. Kravchuk; G.O. Ogar; A.A. Dvorjanskiy (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The goal is to study the dynamics of the development of motor abilities of young athletes and determine the impact of physical fitness on the sports result at the initial stage of sports specialization in Jiu-jitsu. Research participant. 16 young athletes, age 10-11 years, experience of occupations by wrestling 6-10 months took part in research. All subjects studied in one group three times a week for two academic hours. Research methods: analysis of scientific and methodological literature, pedagogical observations, pedagogical testing, methods of mathematical statistics. Results. The study proved the positive impact of Brazilian jiu-jitsu on the harmonious development of the motor abilities of secondary school age boys. Because of the specifics of competitive activity and the features of the training process in jiu-jitsus, the most pronounced positive dynamics is observed in the study of the dynamics of the development of dexterity, flexibility and strength abilities of the muscles of the upper shoulder girdle and hands. Comparison of physical fitness of groups of "leaders" and "outsiders" showed that at the initial stage in jiu-jitsu essential is the level of development of basic physical fitness. It is the representatives of the group of" leaders " who were more successful in the competition, were better physically prepared for all the studied indicators. Summary. Classes of jiu-jitsu contribute to the harmonious development of motor abilities of children of secondary school age. The level of development of motor abilities of young athletes in jiu-jitsus at the initial stage of sports specialization significantly affects the sports result. The most important influence on sports achievements in jiu-jitsu, are flexibility, agility, and power abilities of the muscles of the arms and upper body.